2016
DOI: 10.14814/phy2.13005
|View full text |Cite|
|
Sign up to set email alerts
|

Physical exercise in aging human skeletal muscle increases mitochondrial calcium uniporter expression levels and affects mitochondria dynamics

Abstract: Age‐related sarcopenia is characterized by a progressive loss of muscle mass with decline in specific force, having dramatic consequences on mobility and quality of life in seniors. The etiology of sarcopenia is multifactorial and underlying mechanisms are currently not fully elucidated. Physical exercise is known to have beneficial effects on muscle trophism and force production. Alterations of mitochondrial Ca2+ homeostasis regulated by mitochondrial calcium uniporter (MCU) have been recently shown to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 76 publications
2
58
0
Order By: Relevance
“…MCU plays a significant role in skeletal muscle function, because it is responsible for Ca 2+ entry into mitochondria during muscle contraction . OPA1 controls mitochondrial fusion and effects on mitochondria respiratory efficiency . Both functions are crucial for mitochondrial function maintenance, and mitochondrial dysfunction associated with OPA1 leads to impaired ATP production and reduced force of skeletal muscle .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCU plays a significant role in skeletal muscle function, because it is responsible for Ca 2+ entry into mitochondria during muscle contraction . OPA1 controls mitochondrial fusion and effects on mitochondria respiratory efficiency . Both functions are crucial for mitochondrial function maintenance, and mitochondrial dysfunction associated with OPA1 leads to impaired ATP production and reduced force of skeletal muscle .…”
Section: Discussionmentioning
confidence: 99%
“…On an intracellular level, the EMS-dependent physiological effects on skeletal muscle size and force are associated with enhanced expression of mitochondrial calcium uniporter (MCU) and optic atrophy protein 1 (OPA1). MCU plays a significant role in skeletal muscle function, because it is responsible for Ca 21 entry into mitochondria during muscle contraction (16). OPA1 controls 25,50, and 75% of the segment length from the greater trochanter to the inferior border of the lateral epicondyle of the femur on the right side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This quantitative decline coupled with the qualitative decline in the functionality and structure of the muscular system results in significant implications for the functional capacity of the elderly 33 . These modifications that occur in the muscular system due to the aging process impair the performance of motor skills, directly altering the ability of elderly individuals to perform instrumental and basic activities of daily living and making it difficult to adapt to the environment in which they live 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Optic atrophy 1 (OPA 1) also regulates fusion by shaping the level of inner-membrane ultrastructure and bioenergetics [46]. It has been shown that both electric stimulation and leg press training results in similar adaptation of skeletal muscle in aged subjects, which includes elevated levels of force generation, increased muscle mass, OPA1 and mitochondrial protein contents [47]. Kitaoka and co-workers reported that caloric restriction and endurance training together increased the levels of OPA1 and Mfn1 in rat skeletal muscle [48].…”
Section: Mitochondrial Dynamics In Exercise and Agingmentioning
confidence: 99%